Analysis on Fear of Missing Out (FOMO) and Hedonic Browsing Through E-Commerce Shopee Influence Toward Consumptive Lifestyle on Students in Indonesia: A Study at State Polytechnic of Malang - Laila Dhelfhia Suhendra; Yohan Bakhtiar; Ahmad Saifi Athoillah (JBS Nexus, 2025)
The consumptive behavior of students today is increasingly influenced by technological advancements and the convenience of online shopping through e-commerce platforms like Shopee. This research aims to analyze the influence of Fear of Missing Out (FOMO) and hedonic browsing effects toward consumptive lifestyle. The approach in this research was quantitative with survey method involving 95 student respondents, which were selected as the research sample. The data which was used was primary data which was collected through the distribution of questionnaires and it were analyzed by using multiple linear regression with the assistance of SPSS version 26. The research showed that FOMO and hedonic browsing had positive and significant effect toward the consumptive lifestyle. FOMO drove purchases to keep up with trends and hedonic browsing encouraged for pleasure alone. Students should enhance the self-awareness toward the emotional and psychological influences in online shopping activities, particularly related to the phenomenon of FOMO and hedonic browsing habits, in order to be able to make more rational financial decisions and avoid impulsive consumer behaviors.